2015
DOI: 10.1038/npp.2015.205
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala, Hippocampus, and Ventral Medial Prefrontal Cortex Volumes Differ in Maltreated Youth with and without Chronic Posttraumatic Stress Disorder

Abstract: Posttraumatic stress disorder (PTSD) is considered a disorder of recovery where individuals fail to learn and retain extinction of the traumatic fear response. In maltreated youth, PTSD is common, chronic, and associated with comorbidity. Studies of extinction-related structural volumes (amygdala, hippocampus, anterior cingulate cortex (ACC), and ventral medial prefrontal cortex (vmPFC)) and this stress diathesis, in maltreated youth were not previously investigated. In this cross-sectional study, neuroanatomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
159
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 80 publications
13
159
0
9
Order By: Relevance
“…Previous research has also shown structural and functional disruptions to OFC and ACC in survivors of childhood maltreatment (Kelly et al, 2013; Lim et al, 2014; Teicher et al, 2014) and those with PTSD (Morey et al, 2016; Mueller et al, 2015; Spielberg et al, 2015). We hypothesized that maltreatment would be broadly associated with altered centrality in OFC and in the ACC, particularly children with PTSD as disruptions in these neural networks may increase their vulnerability to the disorder.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous research has also shown structural and functional disruptions to OFC and ACC in survivors of childhood maltreatment (Kelly et al, 2013; Lim et al, 2014; Teicher et al, 2014) and those with PTSD (Morey et al, 2016; Mueller et al, 2015; Spielberg et al, 2015). We hypothesized that maltreatment would be broadly associated with altered centrality in OFC and in the ACC, particularly children with PTSD as disruptions in these neural networks may increase their vulnerability to the disorder.…”
Section: Introductionmentioning
confidence: 91%
“…About 20–30% of maltreated youth meet criteria for chronic posttraumatic stress disorder (PTSD) (McLeer et al, 1998; McLeer and Ruggiero, 1999), which is accompanied by heightened threat response and difficulty inhibiting fear response to traumatic reminders. We recently reported that maltreated youth with chronic PTSD, when compared to maltreated youth without PTSD, have smaller volumes in brain areas associated with fear extinction, emotion and memory processing, including left amygdala, right hippocampus and right ventromedial prefrontal cortex (Morey et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Smaller hippocampal volume (partially) mediated the effect of CM on adolescent depression during a 5-year follow-up (Rao et al, 2010) and behavioural problems in children (Hanson, Nacewicz, et al, 2015). Larger hippocampal volumes, on the other hand, have been related to CM in healthy samples, suggesting a possible marker of resilient functioning (Mehta et al, 2009;Morey et al, 2016;Thomaes et al, 2010;Nim Tottenham et al, 2010;. Indeed, CM was not related with hippocampal volume reductions in resilient adults (i.e.…”
Section: Brain Structurementioning
confidence: 99%
“…Resilient functioning (i.e. the absence of mental health disorders) in those with a history of CM has been related with larger volume of (midline) PFC regions (Morey, Haswell, Hooper, & De Bellis, 2016;Sarah Whittle et al, 2009). Importantly, larger PFC volumes are also implicated in resilient functioning across a range of domains after CM.…”
Section: Brain Structurementioning
confidence: 99%
See 1 more Smart Citation